Sue has 18 sweets.
Tony also has 18 sweets.
Sue gives Tony x sweets.
Sue then eats 5 of her sweets.
Tony then eats half of his sweets.
Write expressions for the number of sweets Sue and Tony now have.

Respuesta :

Answer:

s = 13 - x

t = [tex]\frac{18+x}{2}[/tex]

Step-by-step explanation:

To start out with:

s = 18

t = 18

Sue gives Tony x sweets

s = 18 - x

t = 18 + x

Sue then eats 5 of her sweets

s =  18 - x - 5 = 13 - x

t  = 18 + x

Tony eats half of his sweets

s = 13 - x

t = [tex]\frac{18+x}{2}[/tex]

(Possible constraint that [tex]x\mod 2 = 0[/tex])

ACCESS MORE